Implementation of the Independent Curriculum in Improving the Quality of Education at State Islamic Senior High Schools - Hatija, Muna; In'am, Akhsanul; Khozin; Faridi (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
Implementing the Independent Curriculum is increasingly urgent in efforts to improve the quality of education that is more flexible, relevant, and adaptive to students' needs. However, problems are still related to the effective implementation of the independent curriculum in educational institutions, especially at the Islamic-based madrasa level. The purpose of this study is to describe the implementation strategy of the Independent Curriculum at MAN Palopo, as well as to identify the challenges faced and opportunities that can be optimized. Using a qualitative method with a case study type, this study found several main strategies, such as classroom adjustments, digital skills development through technology, interest-based learning, and intensive teacher training. The main findings show that MAN Palopo has demonstrated a high commitment to implementing the Independent Curriculum, including integrating technology and project-based learning, but faces limited facilities, time management, and teacher training that still needs improvement. The implications of this study include the need to improve facilities and infrastructure, fulfil the need for technological devices, ongoing training for teachers, and more efficient time management to ensure that the implementation of the Independent Curriculum runs optimally and sustainably.